2021
DOI: 10.1021/acs.langmuir.0c03603
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Chemotherapy: Host–Guest Complexes of Heptaplatin-Cucurbit[7]uril toward Colorectal Normal and Tumor Cells

Abstract: Supramolecular chemotherapy is a strategy that is currently used to improve the therapeutic efficacy of traditional chemotherapy while mitigating side effects. Heptaplatin, a platinum chemotherapeutic antitumor drug in colorectal tumors, is traditionally used in the clinic. However, its side effects and low efficiency in killing tumors remain unresolved. Herein, a facile supramolecular chemotherapy platform on account of the host–guest chemistry between cucurbit[7]­uril and the commercially available heptaplat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 46 publications
(137 reference statements)
0
14
0
Order By: Relevance
“…In the previous study, CB [7] itself has almost no cytotoxicity on colorectal tumor cells at a concentration of 50 μM. 24 50 μM ZnO had less toxicity against HCT116 during 4 h (Figure S1). It demonstrated that the CDZ nanocomplex had a higher antitumor activity to HCT116 than dox.…”
Section: ■ Results and Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In the previous study, CB [7] itself has almost no cytotoxicity on colorectal tumor cells at a concentration of 50 μM. 24 50 μM ZnO had less toxicity against HCT116 during 4 h (Figure S1). It demonstrated that the CDZ nanocomplex had a higher antitumor activity to HCT116 than dox.…”
Section: ■ Results and Discussionmentioning
confidence: 79%
“…Confocal laser scanning microscopy (CLSM) was conducted to observe the HCT116 cells incubated with the CDZ nanocomplex and dox for 4 h. The results exhibited more dead colorectal tumor cells treated with CDZ compared with control and dox (Figure ). In the previous study, CB[7] itself has almost no cytotoxicity on colorectal tumor cells at a concentration of 50 μM . 50 μM ZnO had less toxicity against HCT116 during 4 h (Figure S1).…”
Section: Resultsmentioning
confidence: 80%
“…HCT116 cells were cultured with 50 μM CLE or LE drugs, and the intracellular Pt contents were measured with ICP–MS at 4 and 24 h. The intracellular Pt content of the cells treated with CLE was about 18.3-fold that of the cells treated with LE drugs, suggesting that the CLE tremendously enhanced the infiltration of the Pt compound at 4 h, while the intracellular Pt content of the cells treated with CLE was 1.3 times that of the cells treated with LE drugs at 24 h (Figure A). The reason is that glycoluril units linked by methylene bridges of cucurbituril can cross the cell membrane and improve dual drugs for entering cancer cells, while cucurbit­[ n ]­urils have no obvious cytotoxicity in many human cell lines, as well as cucurbit[8]­uril in human umbilical vein endothelial cells (HUVECs) shown in Figure S3. On the basis of the close link between polyamine and cancer, the de novo metabolism of polyamines has caught researchers’ attention concerning the nanocapsules used to wipe out human colorectal cancer cells. , By fitting the titration curve, the interaction between spermidine and CB[8] exhibited an independent binding model, and the binding constant was (1.15 ± 0.15) × 10 5 M –1 (Figure B). The binding affinity between spermidine and CB[8] was almost the same as that between LP + EP and CB[8] [ K a = (3.73 ± 0.36) × 10 5 ] in pH 6.0 solution (Figure S4), and a higher spermidine concentration promoted the occurrence of this release response in the tumor microenvironment .…”
Section: Resultsmentioning
confidence: 99%
“…43 Furthermore, the complex had shown remarkable anticancer activity revealed by its high targetable cytotoxicity against colorectal cancerous cells (HCT116) with minimal adverse effects exerted on normal colorectal cells compared to the free HePt. 43 Moreover, these findings were additionally supported by measuring spermine levels, where HePt@CB [7] nanocomplex could consume higher levels of spermine (413.85 pg/mL), produced by HCT116 cells, as compared to HePt alone (309.85 pg/mL), after 12 h of incubation with 50 μM HePt@CB [7] or HePt alone. The significant increase in spermine uptake by the HePt@CB [7] (competitively displaced by CB [7]), inside HCT116 cells, reflected the higher intracellular release of HePt in exchange.…”
Section: Cb-based Stimuli-responsive Nanovesicles Inmentioning
confidence: 99%